Morphotypes of cone snails (Conus mustelinus), Conidae: a phenetic analysis - S. R. M. Tabugo; S.R. Boco; S.I.G Masangcay, et al. (Computational Ecology and Software, 2018)
This study describes phenotypic differentiation of Conus mustelinus, a gastropod species belonging to Family Conidae through phenetic analysis. There exist a number of morphotypes for this species. Thus, it is valuable to look into the nature and variation of this species. In this study, adult shell color polymorphism was observed and six (6) morphotypes were documented and described. Herewith, M5 and M6 among the morphotypes studied, closely resembled each other. A total of 27 characters were used to construct the character matrix. The important characters were spiral ground color, spiral bands color, body whorl color, band between subshoulder plus central band and aperture coloration. The generated phenogram revealed possible clusters based on overall phenotypic similarity. Describing variation and relationships based on a combination of discrete shell morphological characters proved to be pertinent in identification process thereby, addressing sibling species and cryptic speciation.